2018
DOI: 10.1016/j.jiph.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Zika virus infection among medical doctors in Aceh province, Indonesia

Abstract: Zika virus (ZIKV) infection, a public health emergency of international concern, has recently been confirmed in Indonesia. However, to date, there has been no study to assess how prepared healthcare workers in Indonesia are to confront this emerging infectious disease. The aim of this study was to assess the attitudes of medical doctors in Indonesia towards ZIKV infection and its associated explanatory variables. A cross-sectional self-administered online survey was conducted from 3 May to 3 June 2016 in Aceh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 28 publications
3
36
2
Order By: Relevance
“…Our study found that majority of study participants were female, younger GPs which were in early career which is similar with previous studies (Harapan et al, 2017a;Harapan et al, 2018a;Harapan et al, 2019); suggesting the results might reflect the contemporary condition of GPs in Indonesia. There is only a small percentage of GPs in Indonesia who have good confidence in diagnosing and treating HMPX cases in clinical settings.…”
Section: General Practitioners' Perspective and Associated Factorssupporting
confidence: 90%
See 4 more Smart Citations
“…Our study found that majority of study participants were female, younger GPs which were in early career which is similar with previous studies (Harapan et al, 2017a;Harapan et al, 2018a;Harapan et al, 2019); suggesting the results might reflect the contemporary condition of GPs in Indonesia. There is only a small percentage of GPs in Indonesia who have good confidence in diagnosing and treating HMPX cases in clinical settings.…”
Section: General Practitioners' Perspective and Associated Factorssupporting
confidence: 90%
“…answered three and two questions correctly, respectively). We have used a similar cut-off point to dichotomize variables in previous studies (Harapan et al, 2017a;Harapan et al, 2018a;Harapan et al, 2017b;Harapan et al, 2016;Harapan et al, 2019). A two-step logistic regression analysis was used to explore the potential explanatory variables associated with confidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations